2022
DOI: 10.1111/josh.13144
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Online Bullying and Offline Violence‐Related Behaviors Among a Nationally Representative Sample of US Adolescents, 2011 to 2019

Abstract: BACKGROUND Being bullied online is associated with being bullied in school. However, links between online bullying and violence‐related experiences are minimally understood. We evaluated potential disparities in these associations to illuminate opportunities to reduce school‐based violence. METHODS We used five cohorts of Youth Risk Behavior Survey national cross‐sectional data (2011‐2019, Ntotal = 73 074). We used survey‐weighted logistic and multinomial models to examine links between online bullying and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
(96 reference statements)
0
4
0
2
Order By: Relevance
“…Cyber‐bullying is a relatively novel exposure and its effects on mental health is an area of active study. Recent research has suggested that cyber‐bullying alone is less impactful than face‐to‐face bullying (Hase, Goldberg, Smith, Stuck, & Campain, 2015), and that students who experience cyber‐bullying are also more likely experience face‐to‐face bullying and vice versa (Kreski, Chen, Olfson, Cerdá, Martins, et al., 2022; Odgers & Jensen, 2020a); however, even small increases in both types of bullying experienced by girls at young ages suggests that bullying may be an important driver of growing gender differences in internalizing conditions.…”
Section: Part Iii: Changing Prevalence Of Several Known Risk Factors:...mentioning
confidence: 99%
“…Cyber‐bullying is a relatively novel exposure and its effects on mental health is an area of active study. Recent research has suggested that cyber‐bullying alone is less impactful than face‐to‐face bullying (Hase, Goldberg, Smith, Stuck, & Campain, 2015), and that students who experience cyber‐bullying are also more likely experience face‐to‐face bullying and vice versa (Kreski, Chen, Olfson, Cerdá, Martins, et al., 2022; Odgers & Jensen, 2020a); however, even small increases in both types of bullying experienced by girls at young ages suggests that bullying may be an important driver of growing gender differences in internalizing conditions.…”
Section: Part Iii: Changing Prevalence Of Several Known Risk Factors:...mentioning
confidence: 99%
“…Conversely, dietary components and environmental factors combine to influence a child's behavior, which can result in either positive or negative outcomes (Gallardo-Pujol & Pereda, 2013). In addition, loneliness is a factor in student bullying, suggesting that introverted students are more likely victims of bully because it provides an outlet for their resentment and rage (Kreski et al, 2022). Marginalized groups like immigrants or refugees rarely approach relevant authorities to report bullying encounters.…”
Section: Factors Of Bullyingmentioning
confidence: 99%
“…Despite exploring various aspects and perspectives about bullying, there it still stands as an unresolved phenomenon. Surprisingly, bullying mitigation strategies have received less attention more in developing countries than in the developed nations (Kreski et al, 2022). Internationally, several researches conducted to investigate bullying behavior, however, it received little attention in Pakistan (Hussain & Shah, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Budući da istraživanja sugeriraju kako adolescenti većinu vremena kada su online provode na društvenim mrežama (1,3,4), istraživanja rizičnog online ponašanja adolescenata u svojim početcima fokusirala su se na različite oblike nasilja putem društvenih mreža (npr. vrijeđanje, objavljivanje neistina, slanje neželjenih sadržaja, krađu lozinki, preuzimanje tuđeg identiteta, online isključivanje) (6,10,11). U novije vrijeme kao posebni online rizici za adolescente ističu se ponašanja kojima oni ugrožavaju svoju online privatnost, odnosno privatnost svojih osobnih podataka, a to su komunikacija s nepoznatim osobama i objava sadržaja, osobnih informacija ili fotografija na društvenim mrežama (3,9,(12)(13)(14)(15).…”
Section: Introductionunclassified
“…There are different definitions and types of online risks, and according to the definition of the authors Livingstone and Stoilova (9), online risks for children and young people arise when an adolescent is exposed to potentially harmful online content, such as sexual or violent content; when he/she is the target of a potentially threatening online contact; when he/she is taken advantage of by a potentially harmful contract, such as contract concerning the purchase of certain products or he/she engages in conduct that may be harmful for him/her or another person, such as insults or other forms of verbal violence. Considering that research suggests that adolescents spend most of their online time on social networks (1,3,4), studies of adolescent risky online behavior initially focused on different forms of social media violence (e.g., insults, posting falsehoods, sending unwanted content, password theft, identity theft, online exclusion) (6,10,11). Nowadays, behaviors that endanger their online privacy, i.e.…”
Section: Introductionmentioning
confidence: 99%